Mengenalkan Kegiatan Meronce Pada Anak Usia Dini Sebagai Bentuk Pengembangan Kreativitas - Anggraini, Elya Siska; Sitanggang, Fitri Romasi; Zahara, Siti; Tambun, Tia Rosanna (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the context of creativity, introducing ronce activities to young children is very important because it allows them to understand and apply the basic concepts of creativity in improving creativity skills from an early age. This research aims to explore and analyze how meronce activities can contribute to the development of creativity in early childhood. This research was conducted with children as research subjects. The research method used in this research is a qualitative method. This research uses descriptive data in the form of written or spoken language, and emphasizes process and meaning. The data collection technique is by using the Observation, Observation, Interview, Documentation method. The data analysis technique used is through data reduction, data presentation, drawing conclusions and evaluation. The results of the observations we made were that increasing creativity in early childhood through meronce activities was considered quite good. Because after doing the stringing activity, children are able to choose, arrange and group beads according to their creativity.